PERANCANGAN COMPANY PROFILE SLB AUTIS YPPA PADANG - M.fadil Azry; m.nasrul kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The design of the YPPA Padang Autism SLB Company Profile aims to introduce information to autistic students and their parents. SLB Autism YPPA Padang is a place for teaching and learning (also called classical learning) and an individual learning place for autistic students in the city of Padang, West Sumatra. In addition, in this SLB there is a sensory therapy room, a culinary arts room, a music room, a skills and batik room, a sports room / playing field, a scout room, and a computer room or ICT (Information and Communication Technology). One of inadequacy in the SLB is the lack of company profile media in SLB Autism YPPA Padang, such as not having booklets, signboard, banners, billboards, brochures, and posters that have not been maximized. All these deficiencies were corrected in this design.The design method used starts from the glass box method, while the data analysis method uses SWOT analysis (Strength, Weakness, Opportunity, Threat). The next step is to analyze the product and carry out creative design. The design of the company profile is done by paying attention and displaying layout, typography and attractive colors so that information can be clearly understood.Keywords: Company Profile, Booklet, YPPA Padang Extraordinary Autistic School, Design.